Nonprofit Executive Compensation Levels and their Relationship to Relevant Accounting Based Performance Metrics - Phillips, Janet (Accountancy Business and the Public Interest, 2018)
Keywords: dept.acc; peer-reviewed

The GAAP in Tesla’s Earnings Announcements: A Case Study on the Proliferation of Non-GAAP Financial Measures - Aselta, James; Engel, Russell Paul (The Accounting Educators' Journal, 2018)
The reporting of non-Generally Accepted Accounting Principles Measures (non-GAAP) by U.S. publically traded companies is not new but it has recently come under increased scrutiny by the United States Securities and Exchange Commission (SEC). This case presents a specific example of this scrutiny in the form of Tesla, Inc.’s quarterly earnings announcements and Tesla’s subsequent correspondence with the SEC. This case requires students to answer relevant questions about GAAP vs Non GAAP reporting, generally in the form of a research memo, with references to applicable SEC regulations and guidance on the use and reporting of non-GAAP measures.
Keywords: dept.acc; peer-reviewed

An investigation of nonprofit executive compensation levels and their relationship to relevant accounting based performance metrics - Phillips, Janet F. (Accountancy Business and the Public Interest, 2018)
Keywords: dept.acc; ⛔ No DOI found